Effective Control of Neofusicoccum parvum in Grapevines: Combining Trichoderma spp. with Chemical Fungicides - Aranzazu Gomez-Garay; Sergio Astudillo Calderón; Mª Luisa Tello Mariscal; Beatriz Pintos López (Agronomy)
Vitis vinifera is highly susceptible to grapevine trunk diseases, with Neofusicoccum parvum recognized as a highly destructive pathogen. This study investigates the biocontrol potential of five Trichoderma species (T. harzianum, T. viride, T. asperellum, and T. virens) against N. parvum, evaluating multiple biocontrol mechanisms (mycoparasitism, competition for nutrients, production of volatile organic compounds (VOCs), and antibiosis) as well as their compatibility with the fungicides copper oxychloride and sulfur. Results demonstrated that (1) Trichoderma harzianum effectively suppressed N. parvum through VOC production, mycoparasitism, and nutrient competition, significantly reducing pathogen growth in planta while showing compatibility with both fungicides, highlighting its suitability for integrated disease management; (2) Trichoderma viride showed high inhibition of N. parvum in vitro, but its phytotoxicity in planta limits its field application. These findings support T. harzianum as a promising agent within integrated disease management strategies, offering a sustainable alternative to reduce chemical fungicide reliance in controlling grapevine trunk pathogens.